The impact of maturation level, not chronological age, on attentional control: implications for sports injury prevention in female adolescents - Grinberg, Adam; Hanzlíková, Ivana; Lehnert, Michal; Abdollahipour, Reza (BMC sports science, medicine & rehabilitation, 2024)
BACKGROUND: Non-contact injuries are highly prevalent among young athletes and occur particularly in situations that require fast decision making and divided attention. Administering relevant neurocognitive tests could help identify deficiencies in these cognitive abilities and thus potentially mitigate injury risk. However, processes such as selective attention and response inhibition might depend to some extent on the athlete's maturation stage. We aimed to examine the effect of maturation on selective visual attention and response inhibition among adolescent volleyball players. METHODS: In this cross-sectional study, 52 female adolescents (age 12.3 ± 2.1 years) performed an Eriksen Flankers task. Participants were divided into subgroups based on their estimated adult stature, using the Khamis & Roche method: Pre-pubertal (PRE; n = 13, age: 9.9 ± 1.3), early-puberty (EPUB; n = 7, age: 10.5 ± 0.6), mid-puberty (MPUB; n = 8, age: 12.6 ± 0.8) and late puberty (LPUB; n = 24, age: 14.1 ± 0.9). Analyses of covariance (ANCOVA) were performed on congruent and incongruent reaction times (RT), with corresponding success rates (% correct responses) as covariate. Flanker interference effect was tested using ANOVA. Correlations were further examined between the dependent variables and participants' chronological age. RESULTS: There was a significant group effect, with PRE demonstrating longer RT compared with LPUB (P < 0.001) for both congruent and incongruent RT. Moderate negative correlations were observed between age and RT (Rp = -0.695, Rp = -0.614 for congruent and incongruent RT, respectively) and low positive correlations between age and incongruent success rate (Rs = 0.318). Low to moderate correlations were also observed within the LPUB group for RT (Rp = -0.431--0.532) and success rate (negative Rs = -574 for congruent and positive Rs = 0.417 for incongruent). There were no group differences nor age associations with interference effect. CONCLUSIONS: Our findings indicate that information processing and selective visual attention are superior at late maturation compared with early maturation among female adolescents. The same cannot be said for response inhibition, which did not differ between maturation groups. Similar tendencies were observed with regards to chronological age, but not entirely explained by it. Maturation level, rather than chronological age, should guide practitioners during sport participation and injury prevention programs for young athletes, whose neurocognitive abilities are not yet fully developed, placing them at risk for non-contact injuries.
Keywords: ACL; Injury prevention; Response inhibition; Reaction time; Neurocognitive test; Puberty; Selective attention; Flankers test